IMPROVING INVENTORY MANAGEMENT PRACTICES IN TRANSFORMING THE EFFICIENCY OF HOUSEHOLD EQUIPMENT STORES AT ROYAL MARKET IN SERANG - Khaeruman, Khaeruman; Dewi, Irma Nurmala; Noor, Noorsidi Aizuddin Mat (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
The purpose of this study is to investigate the inventory management practices utilized in household equipment stores located in Pasar Royal, Serang City, as well as the difficulties that store owners encounter when managing their inventory. This study used qualitative research methods, including conducting in-depth interviews, observing, and analyzing documents from within the store. The findings revealed that the retailers utilized various inventory management practices, ranging from straightforward to more organized approaches. Store owners must contend with several obstacles, including inaccurate demand predictions, supply uncertainty, and a need for more efficient inventory management systems. On the other hand, certain stores have implemented improvement strategies, such as Just-in-Time (JIT) methods and the utilization of inventory management software, which have accomplished the goal of increasing both the overall store performance and the operational efficiency of the store. This study emphasizes the importance of better inventory management practices in achieving efficiency transformation in home improvement stores